Monetary Policy Analysis in Backward-Looking Models - Jesper Lindé (Sveriges Riksbank, 2000)
In this paper, I investigate quantitatively how sensitive a typical backward-looking model used in monetary plicy analysis is to the Lucas critique. To do this, I use an equilibrium business cycle model with a Taylor-type rule for nominal money growth. The backward-looking model displays considerable parameter instability, both from a statistical and economic point of view, when the parameters in the estimated monetary policy ruel change. THe findings suggest that the robustness of the conclusions in the literature on the relative merits of an alternative monetary policy rules should be checked in an equilibrium framework.
Keywords: C22; C52; E41; 330; Lucas critique; Real business cycle model; Taylor rules; Aggregate supply; Aggregate demand